Over Expression of Biologically Active Interferon Beta Using Synthetic Gene in E. coli (Journal of Sciences, Islamic Republic of Iran)
In this study, our previously reported novel synthetic gene encoding 166 residues of interferon-? was used for an efficient expression of IFN-?. The synthetic gene was cloned into pET21a expression vector and transferred into E. coli. Recombinant protein was over-expressed in the E. coli. Identity of the recombinant protein was confirmed by western blot analysis. The recombinant protein was biologically active as evaluated by inhibition of cytopathic effect (CPE) formation of Vesicular stomatitis virus (VSV) on the HeLa cells. The effect of three factors including inducer concentration, induction time based on optical density of the culture and induction duration on the expression of rIFN-? was investigated by Taguchi method. Analysis of variance presented that IPTG of 0.5 mM and induction duration of 4 h and induction time of OD600=1 had more effect on IFN-? production. Recombinant IFN-? expression with the above condition yielded 28% of the total E. coli proteins.